2011
DOI: 10.1371/journal.pone.0020283
|View full text |Cite
|
Sign up to set email alerts
|

A Survey Study on Gastrointestinal Parasites of Stray Cats in Northern Region of Nile Delta, Egypt

Abstract: A survey study on gastrointestinal parasites in 113 faecal samples from stray cats collected randomly from Kafrelsheikh province, northern region of Nile delta of Egypt; was conducted in the period between January and May 2010. The overall prevalence was 91%. The results of this study reported seven helminth species: Toxocara cati (9%), Ancylostoma tubaeforme (4%), Toxascaris leonina (5%), Dipylidium caninum (5%), Capillaria spp. (3%), Taenia taeniformis (22%) and Heterophyes heterophyes (3%), four protozoal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 15 publications
8
44
2
1
Order By: Relevance
“…Coman attribute the prevalence of this cestode with the importance of rodent in the diet of these cats (Coman 1972). In our study, the prevalence of the D. caninum was 58 %, which is compatible with the findings of the previous studies done in Brazil (52.6) (Labarthe et al 2004) and Iran (68.1 and 49.5 %) (Arbabi and Hooshyar 2009;Zibaei et al 2007), However, the prevalence of this parasite was higher than the previously recorded rates by other surveys from various countries (Borji et al 2011;Calvete et al 1998;Canto et al 2013;Dalimi and Mobedi 1992;Jittapalapong et al 2007;Khalafalla 2011;Lefkaditis et al 2014;Raji et al 2013;Ramos et al 2013). High prevalence of this parasite in resent survey could be due to the fact that D. caninum requires fleas as intermediary hosts and cats infected after ingesting infected fleas (Labarthe et al 2004).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Coman attribute the prevalence of this cestode with the importance of rodent in the diet of these cats (Coman 1972). In our study, the prevalence of the D. caninum was 58 %, which is compatible with the findings of the previous studies done in Brazil (52.6) (Labarthe et al 2004) and Iran (68.1 and 49.5 %) (Arbabi and Hooshyar 2009;Zibaei et al 2007), However, the prevalence of this parasite was higher than the previously recorded rates by other surveys from various countries (Borji et al 2011;Calvete et al 1998;Canto et al 2013;Dalimi and Mobedi 1992;Jittapalapong et al 2007;Khalafalla 2011;Lefkaditis et al 2014;Raji et al 2013;Ramos et al 2013). High prevalence of this parasite in resent survey could be due to the fact that D. caninum requires fleas as intermediary hosts and cats infected after ingesting infected fleas (Labarthe et al 2004).…”
Section: Discussionsupporting
confidence: 92%
“…M. lineatus was the dominant tapeworm reported in our study with a prevalence rate of 79 % which was higher than that reported in Spain (13.8 %) (Calvete et al 1998), Italy (1.2 %) (Riggio et al 2013), Iran (13.4 and 8 %) (Arbabi and Hooshyar 2009;Borji et al 2011). The T. taeniaeformis prevalence (60 %) was relatively similar to that found by Coman (1972) in Australia (78 %), Stoichev et al (1982) in Bulgaria (75.5 %), Abu-Madi et al (2008) in Qatar (74 %) and Borthakur and Mukharjee (2011) in India (70.4 %) but the prevalence rate of this cestode in our study was higher than that recorded in Spain (8.6 and 22 %) (Calvete et al 1998;Millan and Casanova 2009), Nile Delta of Egypt (22 %) (Khalafalla 2011), Christmas Island (7.14 %) (Adams et al 2008), Greece (8.37 %) (Lefkaditis et al 2014), Mexico (4 %) (Canto et al 2013), Nigeria (6.67 %) (Raji et al 2013), Brazil (0.68 %) (Ramos et al 2013) and Iran (2, 9.6, 15, 12.3 and 9.2 %) (Arbabi and Hooshyar 2009;Borji et al 2011;Changizi et al 2007;Jamshidi et al 2012;Zibaei et al 2007). Coman attribute the prevalence of this cestode with the importance of rodent in the diet of these cats (Coman 1972).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, it was detected at a low incidence in dogs [72] and with an incidence of 5% in stray cats [25]. …”
Section: Prevalence Of Parasitic Zoonoses Among Humans and Animals Inmentioning
confidence: 99%